Manufacture and mechanical characterisation of high voltage insulation for superconducting busbars – (Part 1) Materials selection and development. (April 2017) - Clayton, N.; Crouchen, M.; Devred, A.; Evans, D.; Gung, C.-Y.; Lathwell, I.
Highlights: High voltage insulation for the ITER superconducting bus bars has been selected. Insulation uses a low temperature curing epoxy "pre-preg" on S-glass with a polyimide film. Application techniques developed. Tensile strength of insulation measured at 77 K. Bond strength of insulation to stainless steel at 77 K is reported. Abstract: It is planned that the high voltage electrical insulation on the ITER feeder busbars will consist of interleaved layers of epoxy resin pre-impregnated glass tapes ('pre-preg') and polyimide. In addition to its electrical insulation function, the busbar insulation must have adequate mechanical properties to sustain the loads imposed on it during ITER magnet operation. This paper reports an investigation into suitable materials to manufacture the high voltage insulation for the ITER superconducting busbars and pipework. An R&D programme was undertaken in order to identify suitable pre-preg and polyimide materials from a range of suppliers. Pre-preg materials were obtained from 3 suppliers and used with Kapton HN, to make mouldings using the desired insulation architecture. Two main processing routes for pre-pregs have been investigated, namely vacuum bag processing (out of autoclave processing) and processing using a material with a high coefficient of thermal expansion (silicone rubber), to apply the compaction pressure on the insulation. Insulation should have adequate mechanical properties to cope with the stresses induced by the operating environment and a low void content necessary in a high voltage application. The quality of the mouldings was assessed by mechanical testing at 77 K and by the measurement of the void content.